Kedudukan Hukum Covernote Notaris Terhadap Perlindungan Hukum Bank dalam Perjanjian Kredit - Pradnyasari, Gusti Ayu Putu Wulan; Utama, I Made Arya (Acta Comitas, 2019)
The signing the credit agreement between the bank and the debtor using the guarantee will generally be bound by notarial deed to then in the process of loading the guarantee. Before the guarantee process is completed then the notary will issue Covernote to the bank as creditor. The purpose of this research is to find out how is the Covernote position issued by the notary in the credit agreement of the bank? And how the legal strength of covernote notary is to provide legal protection for banks as creditors in credit agreements. This research uses normative legal research methods. The results showed that the position of Covernote issued by a notary in a bank credit agreement only applies as a statement from a notary / PPAT as the official who made the Covernote who explained that there had been a credit or guarantee binding. Covernote is not proof of collateral, but only as an introduction and temporary evidence is a guide for the bank that will issue credit. Covernote notary does not have the legal force to provide legal protection for banks as creditors in credit agreements in the event of default when the guarantee process is still carried out by a Notary. Penandatanganan perjanjian kredit antara bank dengan debitor yang mempergunakan jaminan pada umumnya akan diikat dengan akta Notaris untuk kemudian diproses pembebanan jaminan. Sebelum proses pembebanan jaminan selesai dilakukan, maka notaris akan mengeluarkan Covernote kepada bank selaku kreditor. Adapun tujuan dari penelitian ini adalah untuk mengetahui bagaimanakah kedudukan Covernote yang dikeluarkan oleh notaris dalam perjanjian kredit bank serta bagaimanakah kekuatan hukum Covernote notaris dalam memberikan perlindungan hukum bagi bank dalam perjanjian kredit. Penelitian ini menggunakan metode  penelitian hukum normatif. Hasil penelitian menunjukan bahwa Kedudukan Covernote yang dikeluarkan oleh notaries/PPAT dalam perjanjian kredit bank hanya sebatas menerangkan bahwa telah terjadi pengikatan kredit atau jaminan. Covernote bukan merupakan bukti agunan namun hanya sebagai keterangan dan bukti yang bersifat sementara sebagai pegangan bagi bank yang akan mengeluarkan kredit. Covernote notaris tidak memiliki kekuatan hukum untuk memberikan perlindungan hukum bagi bank selaku kreditor dalam perjanjian kredit apabila terjadi wanprestasi pada saat proses pembebanan jaminan masih dilakukan oleh Notaris.